PENYULUHAN KENAKALAN REMAJA ANAK SEKOLAH DI SEKOLAH MADRASAH TSANAWIYAH NEGERI 1 KABUPATEN GARUT - Lia Lajuna; Nurlaili Ramli; Nora Liana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
Menstrual hygiene and knowledge among adolescent school girls of Jantho, Aceh Besar-IndonesiaBackground: The age of teenager is the transition period from childhood to adulthood which is characterized by physical, psychological and psycho social changes. One of the biggest changes in adolescents is menstruation. Teens who experience menstruation need to maintain reproductive health. They need special knowledge about menstruation to avoid health problems.Purpose: This study was to analyze the relationship between menstrual hygiene and knowledge among adolescent school girls of Jantho, Aceh Besar-IndonesiaMethods: Type of quantitative research, analytical design using across-sectional approach. the number of samples is 30 people, by purposive random sampling. Data analysis using kendall’s Tau.Results: The results showed that the relationship between menstrual hygiene and knowledge among adolescent school girls of jantho, aceh besar-indonesia, indicated by the value of p value of 0.015 and the value of τ obtained by 0.532. Menstrual hygiene is poor because menstrual hygiene and practice during menstruation was inappropriate due to lack of knowledge, and need more health education in reproductive health and inadequate support for school facilitiesConclusion: The level of knowledge among adolescent school girls of Jantho, Aceh Besar-Indonesia was in poor category. There is a relationship between menstrual hygiene and knowledge among adolescent school girls of Jantho, Aceh Besar-Indonesia Keywords: Menstrual hygiene; Knowledge; Adolescent school girlsPendahuluan: Remaja merupakan periode transisi dari masa anak ke masa dewasa yang ditandai dengan adanya perubahan fisik, psikis dan psikososial. Salah satu perubahan terbesar pada remaja terjadi mentruasi dan rentan terhadap masalah kesehatan. Remaja yang mengalami menstruasi, perlu menjaga pemeliharaan kesehatan reproduksi. Remaja perlu pengetahuan mentruasi agar terhindar dari masalah kesehatan.Tujuan: Mengetahui dan menganalisis hubungan tingkat pengetahuan remaja putri terhadap menstrual hygiene Metode: Jenis penelitian kuantitatif, rancangan analitik menggunakan pendekatan cross-sectional. Jumlah sampel sebanyak 30,dipilih secara purpuse sampling. Analisa data menggunakan uji statistik kendall tau.Hasil: Hasil penelitian menunjukan terdapat hubungan antara tingkat pengetahuan remaja putri tentang menstruasi dengan menstrual hygiene saat menstruasi, ditunjukkan dengan nilai p value sebesar 0,015 dan nilai τ didapatkan 0,532. Menstrual hygiene masih buruk dikarenakan perilaku menstrual hygiene saat menstruasi masih salah. Penyebab lainya karena kurangnya pengetahuan, belum mendapatkan penyuluhan kesehatan reproduksi dan dukungan fasilitas sekolah yang belum memadai.Simpulan: Tingkat pengetahuan wanita muda tentang menstruasi di SMP 2 Kota Jantho termasuk dalam kategori kurang. Ada hubungan antara tingkat pengetahuan remaja putri tentang menstruasi dengan menstrual hygiene saat menstruasi